'RadioAstron'-A telescope with a size of 300 000 km: Main parameters and first observational results - Kardashev, N.; Khartov, V.; Abramov, V.; Avdeev, V.; Alakoz, A.; Aleksandrov, Y.; Ananthakrishnan, S.; Andreyanov, V.; Andrianov, A.; Antonov, N.; Artyukhov, M.; Arkhipov, M.; et al. (2013)
The Russian Academy of Sciences and Federal Space Agency, together with the participation of many international organizations, worked toward the launch of the RadioAstron orbiting space observatory with its onboard 10-m reflector radio telescope from the Baikonur cosmodrome on July 18, 2011. Together with some of the largest ground-based radio telescopes and a set of stations for tracking, collecting, and reducing the data obtained, this space radio telescope forms a multi-antenna ground-space radio interferometer with extremely long baselines, making it possible for the first time to study various objects in the Universe with angular resolutions a million times better than is possible with the human eye. The project is targeted at systematic studies of compact radio-emitting sources and their dynamics. Objects to be studied include supermassive black holes, accretion disks, and relativistic jets in active galactic nuclei, stellar-mass black holes, neutron stars and hypothetical quark stars, regions of formation of stars and planetary systems in our and other galaxies, interplanetary and interstellar plasma, and the gravitational field of the Earth. The results of ground-based and inflight tests of the space radio telescope carried out in both autonomous and ground-space interferometric regimes are reported. The derived characteristics are in agreement with the main requirements of the project. The astrophysical science program has begun. Â© 2013 Pleiades Publishing, Ltd.